PERANCANGAN PROYEK ARSITEKTUR INTERIOR STB SUPERMARKET DI TARAKAN - Caroline, Senny; Kusumowidagdo, Astrid; Indrawan, Stephanus Evert (Universitas Ciputra Surabaya, 2020)
Public awareness for healthy living, especially in big cities is increasing. Increasing economic status andease of access to information and knowledge about healthy lifestyle make people, especially people withmiddle class economies, begin to pay more attention to health. One of the efforts made to start a healthylife is through organic food products. Organic food products are high-quality natural food ingredientscontaining vitamins, fiber, minerals, and other substances that are useful for consuming and consuming.The awareness of these qualities makes the product more organic in demand. Shopping for food needsa common thing for people to do. The development of lifestyle also affects the community in determiningshopping places. The growing age makes retail businesses change the retail concept to be more modern.The concept of supermarkets is now a demand for changes in the lifestyle of the city. The retail conceptis now focused on large and wide sales area outlets and facilities for convenience and comfort that arecomfortable and have an impact on sales. Seeing this developing a supermarket with organic products andpaying attention to the opportunity to develop a supermarket business. The interior architectural designconcept of the STB Supermarket is designed to provide a fresh impression to organic support, which is acombination of centralized and grid circulation patterns, and circulation separation. Supermarket visitors,employees, and management staff can be more effective. Keywords: Healthy Product, Lifestyle, Organic, Retail, Supermarket